Determinan Pengungkapan Kebijakan Anti Korupsi - Mulyono, Hilda Azalia David; Raharja, Surya (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p16, 2023)
Various efforts have been made to prevent and suppress corruption. One of these efforts is by implementing an anti-corruption policy mechanism. The purpose of this study is to re-examine the factors that are thought to influence the disclosure of anti-corruption policies. These variables are the existence of a governance committee, type of industry and company size. The population is public companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021, with a total sample of 2,230 observation data. The research method is quantitative. The analysis used is PLS-SEM. The results of the study show that statistical tests show that the existence of a governance committee, type of industry, and company size have a positive influence on disclosing anti-corruption policies. Keywords: Corruption; Disclosure Of Anti-Corruption; Corporate Governance; Company Characteristics